Applicability of using dynamic MRI to evaluate alleged cranial rhythmic impulse (CRI) - Pezhman Masoudi; Noureddin Karimi; Iraj Abdollahi; Enayatollah Bakhshi; Saeideh Moravej; Ahmad Aghazadeh (BMC Musculoskeletal Disorders)
Abstract Objectives To evaluate the feasibility of using dynamic MRI to measure the features of cranial rhythmic impulse (CRI). Design and setting Fifteen healthy participants (9 females and 6 males, aged 25 to 77) underwent dynamic MRI in a sagittal T2 HASTE view at a rate of 0.60 Hz for 30 s. The MRI videos were analyzed using video tracking software. Three points were marked: the glabella, the midpoint of the sella turcica, and a symmetrical point of the glabella on the occiput. The distances between these points were measured across 46 frames. Amplitudes and rates of asymmetrical CRI waves were calculated using Excel formulas. Results The mean wave frequencies were 5.65 Hz for the anteroposterior distance, 6.2 Hz from sella turcica to occiput, and 6.76 Hz from sella turcica to glabella. The mean wave amplitudes were 0.39 mm, 0.6 mm, and 0.49 mm for the respective distances. Both intraclass correlation coefficients (ICC) and reliability coefficient (R) indicated excellent reliability (R, ICC > 0.90). The technical error of measurement (TEM) exceeded 1 mm for the anteroposterior and sella-to-occiput distances, while it was 0.32 mm for the sella-to-glabella distance. Conclusions Dynamic MRI demonstrates potential in measuring the features of CRI, particularly in assessing CRI wave rate. While the ICC values indicate high reliability, the TEM values suggest that using MRI to measure CRI wave amplitude may only be dependable for the distance from the sella to the glabella.